Creating Smart Connected Learning Ecosystems: A Hybrid Model for Design-Based Learning - Rötkönen Erkki; Winschiers-Theophilus Heike; Goagoses Naska; Zaman Tariq; Itenge Helvi; Tan Daniel Yong Wen; Sutinen Erkki (INTERACTION DESIGN & ARCHITECTURES, 2022)
Emerging technologies and new pedagogies, such as design-based learning, have the potential to revolutionize formal education systems. We postulate that smart learning ecosystems can be co-created through connecting schools and students across the globe to co-design their own virtual learning spaces by exploiting new affordances offered by digital technologies. This paper presents a Hybrid model for Design-Based learning (HyDe), which guides colocated and online design-based learning activities with geographically distributed students. It was conceptualized within a case study, wherein 63 students aged 11 to 13 from three schools in Namibia, Malaysia, and Finland collaborated on co-designing a virtual space to share local perspectives on global challenges. The HyDe model was refined based on reflections from the case study yielding in a model which can be integrated in school curricula across the globe, thereby creating a smart connected learning ecosystem.